Uji Aktivitas Antioksidan Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa bilimbi L.) dengan Metode DPPH - Helen Anjelina Simanjuntak; Ester Angelina Manurung; Herlina Simanjuntak; Nurbaiti Br. Singarimbun; Defacto Firmawati Zega; Lydia Br. Barus; Suharni Pintamas Sinaga (Herbal Medicine Journal, 2026)
Plants contain antioxidants, are easily found around homes, and offer various health benefits, including starfruit, a member of the Oxalidaceae family. The leaves are the plant part used. Empirically, people use them to treat various ailments, including fever, stomach ache, cough, hypertension, rheumatism, headache, diabetes, and pain. Objective to determine the antioxidant activity of ethanol extracts from starfruit (Averrhoa bilimbi L.) leaves and to determine the strength of this activity based on the IC50 using the DPPH method. This study employed an experimental method, including leaf collection, preparation of crude drugs, characterization, phytochemical screening, extraction, preparation of extracts from starfruit leaves, and testing the antioxidant activity of ethanol extracts from starfruit leaves. Examination of the characteristics of the simplicia powder obtained an ethanol-soluble extract content of 29.66%, a water-soluble extract content of 22.66%, a total ash content of 4.0%, an acid-insoluble ash content of 1.83%, and a drying loss of 11.83%. The phytochemical extract screening results contained alkaloids, flavonoids, saponins, and tannins. The results of the antioxidant activity test of starfruit (Averrhoa bilimbi L.) leaf extract with an IC50 value of 39.71983 ppm. The results of this study indicate that starfruit (Averrhoa bilimbi L.) leaf extract has very strong antioxidant activity with an IC50 value of 39.71983 ppm.